Contract Construction and Risk Mitigation In Sharia Bullion Business Activities: Juridical Analysis Of DSN-MUI Fatwa NO. 166/2026 - Fathmah Hanum; Muhammad Lathoif Ghozali (Universitas Islam Darul 'ulum Lamongan, 2026)
The issuance of DSN-MUI Fatwa Number 166/DSN-MUI/II/2026 on Bullion Business Activities Based on Sharia Principles on February 11, 2026, marks a new chapter in gold governance within Indonesia's Islamic financial institutions. This fatwa emerged as a response to the mandates of Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law) and OJK Regulation Number 17 of 2024, which explicitly permit banks—including Islamic banks—to conduct bullion business activities. This study employs a juridical-normative approach to examine two central issues: first, the construction of contracts (akad) for each bullion business activity (gold custody, savings, trading, and financing); second, relevant risk mitigation strategies encompassing market risk, sharia compliance risk, operational risk, and liquidity risk. Analysis reveals that Fatwa No. 166/2026 introduces complementary contract combinations—Wadiah Yad Dhamanah, Mudharabah, Qardh, Murabahah, Rahn, Ijarah, and Wakalah—that collectively accommodate all bullion business lines without violating riba principles. The key instruments of physical qabdh (delivery) and underlying asset guarantees constitute the primary differentiators of Islamic bullion from conventional gold trading practices. This study concludes that the fatwa provides comprehensive legitimacy for Islamic financial institutions to compete in the national gold ecosystem, while recommending integration of real-time information technology systems to ensure ongoing contract transparency.